Au nanocluster-embedded chitosan nanocapsules as labels for the ultrasensitive fluorescence immunoassay of Escherichia coli O157:H7. Issue 17 (31st July 2018) - Cheng, Chang; Yang, Lu; Zhong, Miao; Deng, Wenfang; Tan, Yueming; Xie, Qingji; Yao, Shouzhuo
Abstract : Ultrasensitive fluorescence immunoassay of Escherichia coli O157:H7 is described using Au nanocluster-embedded chitosan nanocapsules as labels. Abstract : Herein, Au nanocluster (AuNC)-embedded chitosan (CS) nanocapsules were prepared and used as a novel signal amplification system for the sensitive fluorescence immunoassay of Escherichia coli O157:H7 ( E. coli O157:H7). AuNCs were embedded in CS to form AuNCs@CS nanocapsules, where a large number of AuNCs were embedded in each nanocapsule. A rapid, ultrasensitive, and selective method for the fluorescence detection of E. coli O157:H7 was developed by coupling the nanocapsule-amplification strategy with immunological recognition and magnetic separation. Compared with a conventional immunoassay using AuNCs as labels, the fluorescence signals of the proposed immunoassay were greatly amplified, because much more fluorescent AuNCs are linked to each bacterial cell. As a result, a linear range was obtained from 3 to 700 CFU mL −1, with a detection limit of 1 CFU mL −1 . This method was successfully used to detect E. coli O157:H7 in drinking water and milk samples.